The impact of smoking on ﬁnger dexterity and dual-task activities in elderly adults: a cross-sectional study - Kaushik, Meenu; Siddiqui, Hammad Ahmed; Chhabra, Charu; Azharuddin, Muhammad (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. Extensive research has focused on the cardiovascular, pulmonary, and cancer-related health consequences of smoking. However, there is a lack of speciﬁc investigations into the consequences of prolonged smoking on human neurocog-nition and neurobiology, particularly related to ﬁnger dexterity and dual-tasking abilities in elderly individuals. Understanding the impact of smoking on dual-tasking conditions and ﬁnger dexterity can provide valuable insights into potential cognitive decline and impairment in daily activities among elderly smokers.Methods. This study recruited 40 subjects based on inclusion and exclusion criteria by convenience sampling of an old age home in Delhi. Participants were divided into elderly smokers (group 1) and non-smokers (group 2) by self-reported smoking status and the results of a Fagerstrom Test for Nicotine Dependence (FTND) questionnaire. Both groups performed dual-task ﬁnger dexterity using the nine-hole peg board (9HPT) and were assessed for task speed and activities of daily living (ADL). ADL was assessed using the Katz Index of Independence in ADL (KATZ). Data were analysed to detect diﬀerences between the groups. Results. The study ﬁndings indicated a statistically signiﬁcant diﬀerence between group 1 and group 2 in the 9HPT (p < 0.05). There were statistically signiﬁcant diﬀerences between group 1 and group 2 in dual-task cognitive 9HPT (C9HPT) and motor 9HPT (M9HPT) tests (p < 0.05). However, analysis using the KATZ found between-group diﬀerences. Conclusions. Smoking had a negative impact on dual-task ﬁnger dexterity, potentially due to its eﬀects on neurocognition and neurobiology.
Keywords: elderly; cognition; activities of daily living; rehabilitation; sedentary lifestyle